FENOMENA KECURANGAN PEMESANAN PADA JASA TRANSPORTASI ONLINE DALAM PERSPEKTIF FRAUD TRIANGLE - Risal Risal; Jaurino Jaurino; Endang Kristiawati Kristiawati; Sartono Sartono; Renny Wulandari (JAD: Jurnal Riset Akuntansi dan Keuangan Dewantara, 2022)
Abstract The background of this research is that online transportation service providers found fraud committed by online transportation drivers, using fake GPS applications, making fictitious orders, and giving the highest star rating. This study aims to analyze the effect of internal control, morality, and pressure on fraudulent ordering behavior in online transportation services. This study uses a quantitative approach. The sampling technique was purposive sampling with a total sample of 100 respondents. The data type is primary data using a questionnaire tested by multiple regression analysis. The study results show that the variables of internal control, morality, and pressure influence online transportation services' fraudulent ordering behavior in Pontianak.